New Species of the Spider Genus Pholcus (Araneae: Pholcidae) from China - Yao, Zhiyuan; Li, Shuqiang (Zootaxa, 2012)
The spider genus Pholcus Walckenaer, 1805 is highly diverse in China. In this study we describe 35 new species: Pholcusabstrusus sp. nov., P. aduncus sp. nov., P. agilis sp. nov., P. alpinus sp. nov., P. bailongensis sp. nov., P. bantouensis sp. nov.,P. bing sp. nov., P. brevis sp. nov., P. chang sp. nov., P. cuneatus sp. nov., P. decorus sp. nov., P. dieban sp. nov., P. ganziensissp. nov., P. huapingensis sp. nov., P. imbricatus sp. nov., P. jiaotu sp. nov., P. kui sp. nov., P. lijiangensis sp. nov., P. liui sp.nov., P. liutu sp. nov., P. mao sp. nov., P. mirabilis sp. nov., P. obscurus sp. nov., P. ovatus sp. nov., P. shuangtu sp. nov., P.tongi sp. nov., P. tuoyuan sp. nov., P. tuyan sp. nov., P. undatus sp. nov., P. wangi sp. nov., P. xiaotu sp. nov., P. yi sp. nov., P. yuantu sp. nov., P. yunnanensis sp. nov. and P. zhui sp. nov. In addition, we provide new illustrations for 45 known species.